SENSITIVITY ISLAMIC STOCK RETURN IN ASIA: THE EFFECT OF EXCHANGE RATE VOLATILITY - Dewanti, Larasayu Anindya; Rusmita, Sylva Alif; Samad, Khairunnisa Abd (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2022)
The current study focuses on the existence of exchange rate volatility that impacts the return of MSCI Islamic stocks in Asia emerging countries. The study also sees comparisons between Islamic emerging markets in Asia (India, China, and Korea) and Southeast Asia regions (Indonesia, Malaysia, Thailand, and the Philippines). This study's daily time series data is from January 2015 to June 2020, employing time series regression as an analysis technique. The EGARCH method is used to indicate the asymmetric model and examines the impact of both good and bad shocks generated. The results highlight that the volatility of the MSINI is statistically positive, whereas MSCNI and MSKRI show a significant adverse effect on volatility. On the other hand, Southeast Asia (MSIDI, MSMYI, MSTHI, and MSPH) has no significant effect on exchange volatility. It is interpreted that the currencies of Southeast Asian countries are not strong enough because they still depend on other exchange rates. This result can be utilized to invest in the Islamic stock market in Southeast Asia because it is not affected by exchange rate volatility. Investors can quickly react to sensitive stocks to avoid uncertainty in stock returns. The government must be advised to increase the fiscal stimulus space and provide ease of business in the real sector.